Contamination of wetland soils and floodplain sediments from agricultural activities in the Cerrado Biome (State of Minas Gerais, Brazil) - Rosolen, Vania Silvia [UNESP]; Campos, Alfredo Borges de; Govone, José Silvio [UNESP]; Rocha, Cleonice (Elsevier B.V., 2015)
The expansion and intensification of agriculture are responsible for the increase in nonpoint pollution and the release of chemical considered toxic to flora, fauna and human health. Since 1970s, the Cerrado Biome in the State of Minas Gerais (Brazil) has been converted to agriculture. This land use change has not been accompanied by research to evaluate pollution levels associated with inorganic elements in natural wetlands and river sediments. In this study samples were collected in natural wetlands and river sediments recently deposited in floodplain areas to determine the total concentration of inorganic compounds that can be considered potentially toxic and to perform risk assessment. The total concentration of 18 elements (As, Ba, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, Sr, Ti, V, Zn and Zr) and oxides present at the organic soil layer (0-30 cm) and at the mineral subsurface horizon (30-60 cm) of the wetlands in the upper oxidized layer (0-10 cm) of sediments was determined by ICP-OES and XRF. Contamination levels were determined and a risk assessment performed by comparing the obtained values with those proposed by the Guidelines for Agricultural Soils of Brazil (CONAMA no. 420) as well as the pedogeochemical background for soils formed from sandstone. The results showed high average concentrations of As, Cr and Cu in soils and floodplain sediments (as well as of Ba, Pb and Ni in some samples) with values exceeding (p significant at 5%) the pedogeochemical background and the threshold value for clean soil established by CONAMA. The concentrations of As and Cr in the soil were above the threshold level in 100% and 60% of samples, respectively, which may impact the environment and living organisms. The calculated contamination index (P-i) indicates that the wetlands exhibit moderate contamination (2 < P-i <= 3) by As > Cr > Cu in the topsoil and in the sub-superficial horizons whereas the floodplain sediments exhibit either no contamination (P-i <= 1) or low level of contamination (1 < P-i <= 2). When compared with sediments, the results suggest that the Cerrado wetland soils have a tendency to acquire pollutants and thus store agrochemicals. This poses a real risk to the environment and living organisms if no BMP are established.
Keywords: Wetland soils; Floodplain sediments; Contamination index; Ecological risk